Relationship of Adolescent Women's Knowledge about Reproductive Health to Adolescent Pregnancy in Kelurahan Baru Ladang Bambu - Lubis, Suriati; Hasanah, Dwi Ris (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2023)
Adolescence comes from the Latin "adolesscere" which means 12-24 years. According to the Indonesian Ministry of Health, adolescents are aged between 10-19 years and have not been married. According to BKKBN is 10-19 years. Teenage pregnancies can face the disgrace of getting pregnant without marriage, feeling guilty about an abortion, or increasing anxiety as the pregnancy gets older. This study aims to determine the relationship between knowledge of Adolescent Women about Reproductive Health and Adolescent Pregnancy. The research methodology in this study is descriptive analytic research with a cross sectional approach. The sample in this study was using accidental sampling as many as 30 people. Based on the results of research on 30 adolescents in the Baru Ladang Baru Village who lacked knowledge as many as 16 people, 53.3% and teenagers who had experienced pregnancy/abortion as many as 6.6%. It can be concluded in this study that there is a relationship between adolescent knowledge about reproductive health and adolescent pregnancy, which means that the lower the knowledge of adolescents, the higher the adolescent pregnancy rate.